New in-situ synthetized hydrogel composite based on alginate and brushite as a potential pH sensitive drug delivery system - Dabiri, Seyed Mohammad Hossein; Lagazzo, Alberto; Barberis, Fabrizio; Shayganpour, Amirreza; Finocchio, Elisabetta; Pastorino, Laura (Carbohydrate polymers, 2017)
•Ibuprofen was loaded on the in-situ synthetized Alginate-brushite hydrogel beads.•Transformation of Na-ibuprofen to its acidic form occurred within the loading procedure.•The brushite within alginate matrix improved mechanical properties.•The brushite crystals restricted swelling behavior of alginate.•The hydrogel composite beads released ibuprofen in a controlled manner. A Series of in-situ alginate-brushite (Alg-Bru) hydrogel composites were fabricated to optimize release profile of ibuprofen (Ibu) and to avoid burst releases associated with the pure form of the hydrogels. The Bru crystals were synthetized and dispersed during the crosslinking process of Alg matrix. The beads with different formulations were subject to various characterization tests such as X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), dynamic mechanical analysis (DMA), and swelling. In addition, the entrapment Efficiency (%EE) and drug release profile were obtained to investigate the impacts of initial concentration of Alg and content of Bru on these parameters. FTIR and XRD outcomes confirmed the successful fabricating of Alg-Bru composite as well as the loading of Ibu. Besides, the results showed that the presence of Bru within Alg matrix restricted polymer chain movement, improved mechanical properties, and decreased swelling ratio. Although the presence of Bru crystals did not improve%EE, they optimized the release profile in a more gradual manner.